Regulador eletrônico de TAP com controlador baseado na plataforma de prototipagem Arduino - GOMES, Alcenir Campelo (2018)
In the searching of efficient energy transmission, many methods are used to ensure the delivery of a high-quality product. This work deals with the creation process of a small system used to regulate the tension levels on home appliances. The main tools utilized and studied were the microcontroller ATmeg328 and the prototyping platform, Arduino. This platform was chosen for making easy the process of building the peripheral circuits and for being cheap and simple to program. Moreover, Arduino has many shields available on marker, which facilitates the building process. Since huge variations happen in the residences’ voltage sources, mainly in those far away from the big energy generators, this project can be locally applied to improve the quality of the voltage in the consumers’ homes.